Characteristics of chicken slaughterhouse wastewater - Yaakob, Maizatul Azrina; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel Ali Saeed; Mohd Kassim, Amir Hashim (AIDIC-Italian Association of Chemical Engineering, 2018)
The chicken slaughterhouse wastewater is a class of wastewater, which is heavily polluted with organic matters including proteins, blood residues, fats and lard. Therefore, the direct discharged of untreated chicken slaughterhouse wastewater into the environment is associated with the occurrence of eutrophication phenomenon. In the present study, the characteristics of chicken slaughterhouse wastewater were investigated to ascertain the role of these wastes in the adverse effect on the environment and natural water system. The parameter tested included biological oxygen demand (BOD), chemical oxygen demand (COD), total suspended solid (TSS), total nitrogen (TN), total organic carbon (TOC), orthophosphate (PO4 3-), temperature and pH. The results revealed available high concentrations of BOD (1,341 - 1,821 ± 242.7 mg L1 ), COD (3,154.19 - 7,719.3 ± 2,282.69 mg L-1), TSS (377.67 - 5,462 ± 2,696.1 mg L-1) which have exceeded the EQA1974 standard limits for disposal of wastewater into the environment. The concentrations of TN (162.6 -563.8 ± 215 mg L-1) and PO4 3- (7.047 - 17.111 ± 4.25 mg L-1) were within the range required for microalgae growth which confirm their role in the occurrence of eutrophication phenomenon. It can be concluded that the direct discharge of chicken slaughterhouse wastewater contributes negatively on the environmental biodiversity and thus they should be subjected for an effective treated before the final disposal.